(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This study examines the role of small business and entrepreneurship in Uzbekistan’s economic stability. It highlights government reforms and legal acts that support small enterprises, reduce tax burdens, and expand access to finance. The findings show that small business contributes more than half of GDP, ensures employment, and promotes regional and macroeconomic stability.